ANALISIS STILISTIKA PADA LIRIK LAGU SHEILA ON 7 DALAM ALBUM MENENTUKAN ARAH SERTA RELEVANSINYA SEBAGAI BAHAN AJAR DI SMP - Rendy Langgeng Tri Yusniar; Yant Mujiyanto; Sri Hastuti (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
This study aims to describe and explain about (1) aspects of diction; (2) aspects of the style of language; (3) aspects of the image; and (4) relevance as teaching material of Indonesian language subjects in junior high school which is in the lyrics of Sheila On 7 in the album Determining the Direction (2008). The type of this research is descriptive qualitative. The results of this study indicate that the lyrics of the song Sheila On 7 album Determine the Direction consists of sentences that can be examined its aspects through stilistic studies. The researchers found the elements contained in the lyrics of this song in the study of stilistika, which consists of diction elements, language style or majas, images, and relevance to teaching materials of Indonesian subjects in SMP class VII. The results of this study also proves that the lyrics of the song Sheila On 7 in the album Determining the Direction can be used as subjects of Indonesian language subjects in junior high school in poetry material.